Method for producing coated electrode active material, and coated electrode active material

JP2025506776APending Publication Date: 2025-03-13BASF SE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024549638
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-22
Filing Date
2023-02-13
Publication Date
2025-03-13

Smart Images

  • Figure 2025506776000001
    Figure 2025506776000001
  • Figure 2025506776000002
    Figure 2025506776000002
  • Figure 2025506776000003
    Figure 2025506776000003
Patent Text Reader

Abstract

1. A method for making a coated cathode active material, comprising the steps of: (a) General formula Li 1+x TM 1-x providing a particulate electrode active material from O2, where T is a combination of metals including Ni and Mn, and optionally at least one element selected from Al, Mg, and transition metals other than Ni and Mn, where x is in the range of 0 to 0.2, and at least 50 mol % of the metal in T is Mn; (b) The particulate electrode active material is mixed with at least one kind of Sn 2+ with an aqueous solution of a salt of (c) removing the water to obtain a solid residue; (d) heat treating the residue obtained from step (c); Includes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a method for manufacturing a semiconductor device comprising the steps of: (a) General formula Li 1+x TM 1-x O 2 providing a particulate electrode active material according to the method of the present invention, wherein T M is a combination of metals comprising Ni and Mn, and optionally at least one element selected from Al, Mg, and transition metals other than Ni and Mn, where x is in the range of 0 to 0.2, and at least 50 mol % of the metal in T M is Mn; (b) The particulate electrode active material is mixed with at least one kind of Sn 2+ with an aqueous solution of a salt of (c) removing the water to obtain a solid residue; (d) heat treating the residue obtained from step (c); The present invention relates to a method for making a coated cathode active material, comprising:

[0002] Additionally, the present invention relates to certain coated cathode active materials. [Background technology]

[0003] Lithium-ion secondary batteries are modern devices for storing energy. Many applications have been considered, from small devices such as mobile phones and laptop computers to car batteries and other e-mobility batteries. Various battery components such as electrolytes, electrode materials and separators have important roles in the performance of the battery. Cathode materials have received particular attention. Several materials have been proposed, such as lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide. Extensive research has been conducted, but the solutions found so far still leave room for improvement.

[0004] Many of the electrode active materials currently under discussion are of the lithiated nickel-cobalt-manganese oxide ("NCM material") or lithiated nickel-cobalt-aluminum oxide ("NCA material") type.

[0005] In a typical process for the preparation of cathode materials for lithium-ion batteries, a so-called precursor is first formed by co-precipitating a transition metal as a carbonate, oxide or, preferably, as an (oxy)hydroxide. This precursor is then mixed with a lithium compound, e.g., LiOH, Li 2 O or Li 2 CO 3 (including but not limited to) and calcined at high temperature. The lithium compound(s) can be used as hydrate(s) or in dehydrated form. Calcination or calcination, also commonly referred to as thermal or heat treatment of the precursor, is usually carried out at temperatures ranging from 600 to 1000°C. If hydroxides or carbonates are used as precursors, removal of water or carbon dioxide is carried out first, followed by the lithiation reaction. The heat treatment is carried out in the heated zone of an oven or kiln.

[0006] Extensive research has been conducted to improve various properties of cathode active materials, such as energy density, charge / discharge performance such as capacity loss, etc. However, many cathode active materials suffer from limited cycle life and voltage loss, especially for many Mn-rich cathode active materials.

[0007] Certain high manganese materials having high energy density retention are disclosed in EP 3 486 980. However, the disclosed cathode active materials suffer from such limited energy density.

[0008] However, it has been observed that high manganese cathode active materials suffer from Mn dissolution during repeated cycling. Thus, increasing manganese content is detected in the electrolyte and on the anode. Continued manganese dissolution can lead to degradation of the anode protection layer (also called the solid electrolyte interface), causing parasitic consumption of active lithium, and ultimately causing reversible (cyclable) capacity loss and cell failure. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] EP 3 486 980 Summary of the Invention [Problem to be solved by the invention]

[0010] It was therefore an object of the present invention to provide an electrochemical cell having high energy density retention while having a reduced tendency to capacity loss due to manganese dissolution. [Means for solving the problem]

[0011] We have therefore found a method as defined at the outset, hereinafter also referred to as the method of the invention or the method according to the (present) invention. The method of the invention comprises steps (a), (b), (c) and (d). Step (a) is also referred to as (a). Step (b) is also referred to as (b). Step (c) is also referred to as (c). Step (d) is also referred to as (d). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In step (a), the particulate electrode active material is a compound represented by the general formula Li 1+x TM 1-x O 2wherein TM is a combination of metals comprising Ni and Mn, and optionally at least one element selected from Al, Mg, and transition metals other than Ni and Mn, where x is in the range of 0.1-0.2, and at least 50 mol %, preferably 50-85 mol %, of the metal in TM is Mn.

[0013] In one embodiment of the present invention, the particulate electrode active material provided in step (a) has an average particle size (D50) in the range of 3 to 20 μm, preferably 5 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction. The particles are usually composed of aggregates from primary particles, and the particle size mentioned above refers to the particle size of the secondary particles.

[0014] In one embodiment of the present invention, the particulate electrode active material provided in step (a) has a particle size of 1.0 to 10.0 m 2 / g, which can be determined by nitrogen adsorption after outgassing the sample at 200 ° C for 30 min and beyond, according to DIN ISO 9277:2010.

[0015] In a preferred embodiment of the present invention, T in the particulate electrode active material provided in step (a) is a combination of elements of general formula (I): (Ni a Co b Mn c ) 1-d M 1 d (I) (In the formula, a is in the range of 0.20 to 0.40, preferably 0.25 to 0.35, b is 0 or in the range of 0.01 to 0.20, preferably 0 or in the range of 0.05 to 0.15; c is in the range of 0.50 to 0.85, preferably 0.60 to 0.70; d is in the range of 0 to 0.02; M 1 is selected from Al, Ti, Zr, W, Mo, Mg, Nb, and combinations of at least two of the foregoing; a+b+c=1).

[0016] Preferably, a>b.

[0017] The particulate electrode active material provided in step (a) may be coated or uncoated, but is preferably uncoated.

[0018] Some metals are ubiquitous, e.g. sodium, calcium or zinc, and trace amounts of them are present practically everywhere, but such trace amounts are not taken into account in the present specification, trace amounts in this context meaning amounts of 0.02 mol % or less with respect to the total metal content TM.

[0019] In step (b), the particulate electrode active material provided in step (a) is treated with at least one Sn 2+ Salts of, for example, SnSO 4 Treat with an aqueous solution of.

[0020] The aqueous solution may have a Sn concentration in the range of 0.1 to 3 mass %, preferably 0.3 to 1 mass %.

[0021] In one embodiment of the invention, the treating is carried out by combining the aqueous solution with the particulate electrode active material provided in step (a) and allowing them to interact with each other.

[0022] In one embodiment of the present invention, the volume ratio of the aqueous solution containing a Sn salt to the electrode active material provided in step (a) is in the range of 30:1 to 20:1.

[0023] Step (b) may be supported by mixing operations such as stirring, shaking, sonication under stirring, etc.

[0024] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of +5 to 85°C, preferably 20 to 50°C.

[0025] The pressure under which step (b) is carried out is generally not critical: normal pressure is preferred.

[0026] In one embodiment of the invention, step (b) has a duration in the range of 1 to 24 hours.

[0027] Step (c) involves removing the water, thereby obtaining a solid residue. The removal of water can be carried out by solid-liquid separation techniques, such as filtration or centrifugation, or by evaporation of the water, evaporation being preferred.

[0028] In one embodiment of the present invention, step (b) is carried out in the same vessel as step (c), for example in a stirred suction filter (in German "Ruehrfilternutsche"), and the electrode active material provided in step (a) and Sn 2+ Filtration begins 1 to 5 minutes after combination with the aqueous salt solution.

[0029] The evaporation of water can be carried out at a temperature ranging from 60 to 150° C., preferably from 80 to 120° C. The evaporation can be carried out for a duration ranging from 1 to 72 hours.

[0030] Evaporation of water may be supported by carrying out step (c) at reduced pressure, for example from 1 to 500 mbar (abs), preferably from 2 to 100 mbar (abs).

[0031] From step (c) a solid residue is obtained, preferably having the appearance of a moist powder.

[0032] In one embodiment of the present invention, step (d) is carried out at a temperature in the range of 400 to 750°C, preferably 450 to 550°C.

[0033] In one embodiment of the present invention, the temperature is increased before reaching the desired temperature of 400-750° C., preferably 450-550° C. For example, the solid residue of step (c) is first heated to a temperature of 250-350° C. and kept constant for a time period of 10 min-4 h, then increased to 400-750° C. and kept constant for a time period of 10 min-14 h.

[0034] In one embodiment of the present invention, the heating rate in step (d) is in the range of 0.1 to 10° C. / min.

[0035] In one embodiment of the present invention, step (d) is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln, or a combination of at least two of them. A rotary kiln has the advantage that the homogenization of the material produced therein is very good. In roller hearth kilns and pusher kilns, different reaction conditions for different steps can be set very easily. In laboratory scale experiments, box furnaces, tube furnaces, split tube furnaces and muffle furnaces can also be used.

[0036] In one embodiment of the present invention, step (d) is carried out in an oxygen-containing atmosphere, such as a nitrogen-air mixture, a noble gas-oxygen mixture, air, oxygen or oxygen-enriched air. In a preferred embodiment, the atmosphere in step (d) is selected from air, oxygen and oxygen-enriched air. The oxygen-enriched air can be, for example, a 50:50 volumetric ratio of air and oxygen. Other options include a 1:2 volumetric ratio of air and oxygen, a 1:3 volumetric ratio of air and oxygen, a 2:1 volumetric ratio of air and oxygen, and a 3:1 volumetric ratio of air and oxygen.

[0037] In one embodiment of the invention, step (d) is carried out under an atmosphere of an inert gas, such as nitrogen.

[0038] In one embodiment of the invention, step (d) comprises the step of: 2 The reaction is carried out in an atmosphere having a carbon dioxide content in the range of, for example, 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. 2The content can be determined by optical methods, for example using infrared light. It is even more preferred to carry out step (c) under an atmosphere having a carbon dioxide content below the detection limit of optical methods, for example based on infrared light.

[0039] In one embodiment of the invention, step (d) has a duration ranging from 1 to 30 hours. Preferably, it is from 60 minutes to 6 hours. The cooling time is ignored in this context.

[0040] After the heat treatment according to step (d), the coated electrode active material thus obtained is cooled before further processing.

[0041] The cathode active material of the present invention can be obtained by the method of the present invention. Without wishing to be bound by any theory, it is believed that the heat treatment 2 is cut, and Sn 2+ For example, SnO 2 It is believed that the SnO 2 It is preferable to capture

[0042] The cathode active materials of the present invention exhibit excellent properties, particularly with respect to cycling stability and low capacity loss.

[0043] A further aspect relates to a specific cathode active material, hereinafter also referred to as the cathode active material of the present invention. The cathode active material of the present invention has the general formula LiNi 0.5 Mn 1.5 O 4 , or Li 1+x TM 1-x O 2 Core made of SnO 2 wherein TM is a combination of metals including N and Mn, and optionally at least one element selected from Al, Mg, and transition metals other than Ni and Mn, where x is in the range of 0 to 0.35, and at least 50 mol % of the metal in TM is Mn. In certain embodiments, the shell is SnO 2 It is.

[0044] In the context of the present invention, the cathode active material of the present invention has the general formula Li 1+x TM 1-x O 2 where x is in the range of 0-0.35, preferably 0.12-0.20, TM contains two or more transition metals, and at least 50 mol % of TM is Mn, preferably 50-85 mol %, preferably 60-70 mol % is Mn. The cathode active material of the present invention further comprises SnO 2 The shell comprises:

[0045] In one embodiment of the present invention, Li 1+x TM 1-x O 2 where TM is a metal combination of general formula (I): (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.20 to 0.40, preferably 0.25 to 0.35, b is 0 or in the range of 0.01 to 0.20, preferably 0 or in the range of 0.05 to 0.15; c is in the range of 0.50 to 0.85, preferably 0.60 to 0.70; d is in the range of 0 to 0.02; M is at least one of Al, Mg, Ti, Mo, W, Nb, and Zr; a+b+c=1).

[0046] In one embodiment of the present invention, the cathode active material of the present invention has an average particle size (D50) in the range of 3 to 20 μm.

[0047] In one embodiment of the invention, the shell in the cathode active material of the invention has a thickness in the range of 5 to 10 nm. The thickness can be determined by transmission electron microscopy ("TEM").

[0048] A further aspect of the present invention relates to electrodes comprising at least one electrode active material according to the present invention. These are particularly useful for lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the present invention exhibit good discharge behavior. Electrodes comprising at least one electrode active material according to the present invention are also referred to as cathodes according to the present invention or cathodes according to the present invention below.

[0049] In particular, the cathode of the present invention comprises (A) at least one cathode active material of the present invention; (B) Carbon in a conductive state; (C) a binder polymer, also called binder or binder (C), and preferably (D) Current collector Contains:

[0050] In a preferred embodiment, the cathode of the present invention comprises, based on the sum of (A), (B) and (C), (A) 80 to 98% by mass of the cathode active material of the present invention; (B) 1 to 17 mass% carbon, (C) 1 to 15% by mass of a binder polymer Contains:

[0051] The cathodes according to the present invention may include additional components. They may include a current collector, such as, but not limited to, aluminum foil. They may further include conductive carbon and a binder.

[0052] The cathode according to the present invention contains a conductively modified carbon, also called carbon (B) for short, which can be selected from soot, activated carbon, carbon nanotubes, graphene, graphite, and a combination of at least two of the foregoing.

[0053] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. Polyisoprene and polyacrylates are furthermore suitable. Polyacrylonitrile is particularly preferred.

[0054] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.

[0055] In the context of the present invention, polyethylene refers not only to homopolyethylenes, but also to polyethylenes containing at least 50 mol % copolymerized ethylene and up to 50 mol % of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutene, vinyl aromatics, such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C 10 copolymers of (meth)acrylic acid. 1 ~C 10 -alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also copolymers of ethylene with maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.

[0056] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene, and α-olefins, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic polypropylene or essentially isotactic polypropylene.

[0057] In the context of the present invention, polystyrene refers to homopolymers of styrene as well as acrylonitrile, 1,3-butadiene, (meth)acrylic acid, C 2 styrene, 1,3-butadiene, (meth)acrylic acid, 1 ~C 10 -alkyl esters, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene copolymers are also understood to mean.

[0058] Another preferred binder (C) is polybutadiene.

[0059] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.

[0060] In one embodiment of the invention, the binder (C) has an average molecular weight M ranging from 50,000 g / mol to 1,000,000 g / mol, preferably up to 500,000 g / mol. W The (co)polymers are selected from those having the formula:

[0061] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.

[0062] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers.Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule.Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-chlorofluoroethylene copolymer.

[0063] Suitable binders (C) are especially polyvinyl alcohol and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.

[0064] The cathode of the present invention may contain 1 to 15% by weight of binder(s) relative to the electrode active material. In other embodiments, the cathode of the present invention may contain 0.1 to less than 1% by weight of binder(s).

[0065] A further aspect of the invention is a battery containing at least one cathode comprising the electrode active material of the invention, carbon and a binder, at least one anode, and at least one electrolyte.

[0066] The cathode embodiments of the present invention have already been described in detail above.

[0067] The anode is made of at least one anode active material, such as carbon (graphite), TiO 2 , lithium titanium oxide, silicon or tin. The anode may further comprise a current collector, for example a metal foil, such as copper foil.

[0068] The electrolyte may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally, additives.

[0069] The non-aqueous solvent for the electrolyte can be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.

[0070] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C 1 ~C 4 -alkylene glycols, and in particular polyethylene glycols, where the polyethylene glycols are those containing up to 20 mol % of one or more C 1 ~C 4 The polyalkylene glycol may preferably be a polyalkylene glycol having two methyl or ethyl end caps.

[0071] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W may be at least 400 g / mol.

[0072] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W can be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.

[0073] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, with 1,2-dimethoxyethane being preferred.

[0074] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.

[0075] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.

[0076] An example of a suitable cyclic acetal is 1,3-dioxane, and especially 1,3-dioxolane.

[0077] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0078] Examples of suitable cyclic organic carbonates are compounds according to the general formulae (II) and (III): [ka] (In the formula, R 1 , R 2 and R 3 can be the same or different, hydrogen, and C 1 ~C 4 -alkyl, for example selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, preferably R 2 and R 3 (Both cannot be tert-butyl).

[0079] In a particularly preferred embodiment, R 1 is methyl, R 2 and R 3 are each hydrogen or R 1 , R 2 and R 3Each is hydrogen. In another embodiment, R 1 is fluorine, R 2 and R 3 are hydrogen.

[0080] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).

[0081] [ka]

[0082] Preferably, the solvent or solvents are used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.

[0083] The electrolyte further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. An example of a suitable lithium salt is LiPF 6 , LiBF 4 , LiClO 4 , LiAsF 6 , LiCF 3 SO 3 , LiC(C n F 2n+1 SO 2 ) 3 , lithium imide, e.g. LiN(C n F 2n+1 SO 2 ) 2 (wherein n is an integer ranging from 1 to 20), LiN(SO 2 F) 2 , Li 2 SiF 6 , LiSbF 6 , LiAlCl 4 and the general formula (C n F 2n+1 SO 2 ) t It is the salt of YLi. where t=1 when Y is selected from oxygen and sulfur; when Y is selected from nitrogen and phosphorus, t=2; When Y is selected from carbon and silicon, t=3).

[0084] The preferred electrolyte salt is LiC(CF 3 SO 2 ) 3 , LiN(CF 3 SO 2 ) 2 , LiPF 6 , LiBF 4 , LiClO 4 Selected from LiPF 6 and LiN(CF 3 SO 2 ) 2 is particularly preferred.

[0085] In one embodiment of the present invention, the battery according to the present invention comprises one or more separators by which the electrodes are mechanically separated.Suitable separators are polymer films, especially porous polymer films, that are unreactive towards metallic lithium.Particularly suitable materials for the separators are polyolefins, especially film-forming porous polyethylene and film-forming porous polypropylene.

[0086] A separator made of polyolefin, particularly polyethylene or polypropylene, may have a porosity in the range of 35 to 45%. A suitable pore size is, for example, in the range of 30 to 500 nm.

[0087] In another embodiment of the present invention, the separator can be selected from PET nonwoven fabrics filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.

[0088] The battery according to the invention further comprises a housing which may have any shape, for example a cube, or the shape of a cylindrical disk or can. In one variant, a metal foil configured as a pouch is used as the housing.

[0089] The battery according to the invention exhibits good discharge behaviour, for example very good discharge and cycling behaviour at low temperatures (below 0° C., for example −10° C. or less).

[0090] The battery according to the present invention may comprise two or more electrochemical cells that are combined with each other, for example, connected in series or connected in parallel. A series connection is preferred. In the battery according to the present invention, at least one electrochemical cell contains at least one cathode according to the present invention. Preferably, in the electrochemical cell according to the present invention, the majority of the electrochemical cells contain the cathode according to the present invention. Even more preferably, in the battery according to the present invention, all the electrochemical cells contain the cathode according to the present invention.

[0091] The present invention further provides a method for using the battery according to the present invention in equipment, especially mobile equipment.Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships.Other examples of mobile equipment are manually operated, such as computers, especially laptops, phones, or powered hand tools, for example in the construction sector, especially drills, battery-powered drivers, or battery-powered staplers. EXAMPLES

[0092] The present invention is further illustrated by the following examples.

[0093] The average particle size (D50) was determined by dynamic light scattering ("DLS"). Percentages are by weight unless otherwise stated.

[0094] LiOH H 2 O was purchased from Rockwood Lithium. SnSO 4 was purchased from Aldrich.

[0095] Step (d) was carried out in a tube furnace, type: Nabertherm model RS80 / 500 / 13.

[0096] Unless otherwise stated, all synthetic steps were carried out in a glove box (MB200B, MBraun) under an argon atmosphere with oxygen and water concentrations below 0.1 ppm.

[0097] I. Preparation of the Cathode Active Material CAM.1 of the Invention I.1 Step (a.1): Preparation of uncoated electrode active material A stirred tank reactor was charged with deionized water and heated to 55°C. The pH value was adjusted to 8.05 by adding aqueous sodium hydroxide. The coprecipitation reaction was started by simultaneously feeding aqueous solutions of transition metal sulfate and sodium carbonate at a flow ratio of 1.3 and a mean residence time of 13.5 hours at total flow rate. The aqueous transition metal solution contained Ni and Mn in a molar ratio of 1:2 and a total transition metal concentration of 1.65 mol / kg. The aqueous sodium carbonate solution was a 27% by weight aqueous sodium carbonate solution. The pH value was maintained at 8.05 by separately feeding aqueous sodium carbonate. Starting from the start of all feeds, the mother liquor was continuously removed. The resulting suspension was filtered, washed with distilled water, dried in air at 120°C and sieved to isolate the precursor of mixed transition metal carbonate, TMCO. 3 obtained.

[0098] TMCO 3 Li 2 CO 3 and in a Li / (TM) molar ratio of 1.30. The mixture was heated to 930 °C and kept in a forced flow of a mixture of 20% oxygen and 80% nitrogen (by volume) for 5 h. After cooling to room temperature, the resulting powder was deagglomerated and sieved through a 32 μm mesh to obtain the basic material B-CAM.1.

[0099] I.2 Preparation of coated electrode active material Process (b.1): SnSO 4 Treatment with an aqueous solution of First, 0.14 g of 3.0 wt.% SnSO was sonicated for 20 min (using an Elma model Elmasonic P 60H sonicator). 4was dispersed in 70 ml of deionized water. Then, 10 g of B.CAM (BASF) powder was added to the solution, sonicated for 10 minutes, and then stirred at room temperature for 3 hours.

[0100] Step (c.1): Removal of water The water was then removed under vacuum using a Memmert oven (model UFE 400) at 80° C. for 48 hours.

[0101] Step (d.1): Heat treatment The powder obtained in step (c.1) was calcined in a tube furnace (Nabertherm model RS 80 / 500 / 13). The powder was heated to 500°C at a rate of 2°C / min and maintained at 500°C for 5 hours under air atmosphere. After that, the heating was stopped and the calcined powder was cooled to room temperature. The coated cathode active material CAM.1 of the present invention was obtained, which is composed of SnO 2 The coating contained

[0102] II. Electrochemical Testing II.1 Cathode fabrication General steps: Cathode: PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 10 wt% solution. For electrode preparation, binder solution (3.5 wt%), carbon black (Super C65, 4 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), inventive CAM.1 or comparative cathode active material B-CAM.1 (92.5 wt%) was added and the suspension was mixed again to obtain a lump-free slurry. The slurry was coated on a 15 μm thick Al foil using an Erichsen autocoater, followed by drying at 120 °C for 15 min at normal pressure and then at 120 °C for 4 h in vacuum. The loading was 8-10 mg / cm 2 All electrodes were dried at 120° C. for 12 h. All electrodes were calendered before further use.

[0103] A glass fiber separator was used, available from Whatmann Inc. A lithium anode was used.

[0104] II.2 Coin Cell Manufacturing A coin-shaped half-cell (20 mm in diameter and 3.2 mm in thickness) containing the cathode prepared as described in II.1 and lithium metal as working and counter electrodes, respectively, was assembled and sealed in an Ar-filled glove box. The cathode, anode, and separator were then stacked in the order of cathode / separator / Li foil to fabricate a half-coin cell. Then, 1.0 M LiPF in EC:EMC (ethylene carbonate:ethyl methyl carbonate) with a mass ratio of 3:7 was added to the half-coin cell. 6 0.1 mL of electrolyte was added.

[0105] II.3 Testing LiB Test Protocol: Typically, in every experiment, at least three cells were successfully cycled and the results presented are the average of these cells, which were cycled at 25°C using a battery testing system (Landt Potentiostat; Landt International Inc.).

[0106] [Table 1]

Claims

1. The following steps: (a) General formula Li 1+x T.M. 1-x O 2 providing a particulate electrode active material according to the formula (1), wherein T is a combination of metals comprising Ni and Mn, and optionally at least one element selected from Al, Mg, and transition metals other than Ni and Mn, where x is in the range of 0 to 0.35, and at least 50 mol % of the metals in T is Mn; (b) The particulate electrode active material is mixed with at least one Sn 2+ with an aqueous solution of a salt of (c) removing the water to obtain a solid residue; (d) heat treating the residue obtained from step (c); A method for making a coated cathode active material, comprising:

2. The electrode active material provided in step (a) has the formula Li 1+x T.M. 1-x O 2 wherein TM is of general formula (I): (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.2 to 0.4; b is 0 or in the range of 0.01 to 0.20; c is in the range of 0.55 to 0.8; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, Nb, and Zr; a + b + c = 1) The method of claim 1, wherein the metal combination is

3. Sn added in step (b) 2+ The salt is SnSO 4 The method according to claim 1 or 2,

4. 3. The method of claim 1 or 2, wherein step (d) comprises a calcination step at a maximum temperature in the range of 400 to 600°C.

5. 3. The process according to claim 1 or 2, wherein step (d) comprises a drying step at a maximum temperature in the range of from 40 to 250°C.

6. The method according to claim 1 or 2, wherein the particulate electrode active material has an average particle size (d50) in the range of 3 to 20 μm.

7. General formula Li 1+x T.M. 1-x O 2 and a core of SnO 2 wherein TM is a combination of metals including Ni and Mn, and optionally at least one element selected from Al, Mg, and transition metals other than Ni and Mn, x is in the range of 0 to 0.35, and at least 50 mol % of the metal in TM is Mn.

8. The core has the formula Li 1+x T.M. 1-x O 2 where TM corresponds to the general formula (I): (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.2 to 0.4; b is 0 or in the range of 0.01 to 0.20; c is in the range of 0.55 to 0.8; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, Nb, and Zr; a + b + c = 1) The particulate cathode active material of claim 7 , wherein the metal combination is:

9. 8. The particulate cathode active material of claim 7 having an average particle size (d50) in the range of 3 to 20 μm.

10. 8. The particulate cathode active material of claim 7, wherein the shell has a thickness in the range of 5 to 10 nm.

11. (A) at least one particulate cathode active material according to claim 7; (B) carbon in a conductive state; and (C) Binder polymer a cathode.

12. Based on the sum of (A), (B), and (C), (A) 80 to 98 wt. % of the cathode active material of the present invention; (B) 1 to 17% by mass of carbon; (C) 1 to 15% by mass of a binder polymer The cathode of claim 11 comprising:

13. 12. An electrochemical cell comprising at least one cathode according to claim 11.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery

    EP3486980A1